Prostate Cancer Screening Behaviors Based on the Health Belief Model in Men Aged 40-70 Years in Fasa City, Fars Province, Iran, in 2019 - Ali Khani Jeihooni; Mehdi Amirkhani; Hamideh Mirshekari; Seyyed Mansour Kashfi (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Prostate cancer (PC) is the fourth most common and the second deadly cancer in the world. Various theories have been proposed to identify the characteristics of individuals and their surrounding environments that somehow affect their behaviors. The health belief model (HBM) is one of the theories that are useful for studying health problems and designing programs to prevent diseases and injuries. Objectives: The purpose of this study was to determine PC screening behaviors based on HBM in men aged 40-70 years old in Fasa city, Fars province, Iran. Methods: This was a descriptive, analytical, and cross-sectional study performed on 400 men aged 40-70 years in 2019. The data collection instrument was a standard questionnaire used in Anderson's study, whose validity and reliability have been confirmed. Data were analyzed by SPSS 22 using descriptive (frequency, mean, and standard deviation) and inferential (the Pearson correlation coefficient and linear regression) statistics at the significance level of p<0.05. Results: The mean age of the participants in this study was 54.24±5.46 years. The mean number of children was 2.84±1.84. According to the results, perceived susceptibility, perceived severity, and perceived self-efficacy positively correlated with PC screening behaviors, and there was a significant inverse relationship between perceived barriers and PC screening behaviors. Conclusion: The use of behavioral models such as HBM can be useful to implement appropriate plans to encourage PC screening behaviors.